PENGARUH PENDAPATAN, LOKUS PENGENDALIAN DAN PENGETAHUAN KEUANGAN TERHADAP PERILAKU KEUANGAN PELAKU UMKM KECAMATAN CINERE - Yusnia Yusnia; Jubaedah Jubaedah (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
This research conducted to determine the influence of income, locus of control and financial knowledge against financial behavior agents sub-district cinere umkm.The population in this research is kecamatan cinere depok city as many as 30 sub-district agents cinere umkm .The sample collection was done using saturated sample which means all of the population as sample, so that elected 30 respondents from a population that has been registered. Data was gathered using techniques or poll questionnaires Testing data analysis in the test validity and reliability test use application spss and analysis hypothesis in this research using analysis partial least square (PLS) with program smartpls version 3.0. The results showed that (1) income influences financial behavior, (2) locus of control financial impact on behavior, (3) knowledge financial impact on financial behavior.